MODELING CONTROLLED ASYNCHRONOUS ELECTRIC DRIVES WITH MATCHING REDUCERS AND TRANSFORMERS - V. S. Petrushin (National Technical University "Kharkiv Polytechnic Institute", 2015)
Purpose. Working out of mathematical models of the speed-controlled induction electric drives ensuring joint consideration of transformers, motors and loadings, and also matching reducers and transformers, both in static, and in dynamic regimes for the analysis of their operating characteristics. Methodology. At mathematical modelling are considered functional, mass, dimensional and cost indexes of reducers and transformers that allows observing engineering and economic aspects of speed-controlled induction electric drives. The mathematical models used for examination of the transitive electromagnetic and electromechanical processes, are grounded on systems of nonlinear differential equations with nonlinear coefficients (parameters of equivalent circuits of motors), varying in each operating point, including owing to appearances of saturation of magnetic system and current displacement in a winding of a rotor of an induction motor. For the purpose of raise of level of adequacy of models a magnetic circuit iron, additional and mechanical losses are considered. Results. Modelling of the several speed-controlled induction electric drives, different by components, but working on a loading equal on character, magnitude and a demanded control range is executed. At use of characteristic families including mechanical, at various parameters of regulating on which performances of the load mechanism are superimposed, the adjusting characteristics representing dependences of a modification of electrical, energy and thermal magnitudes from an angular speed of motors are gained. Originality. The offered complex models of speed-controlled induction electric drives with matching reducers and transformers, give the chance to realize well-founded sampling of components of drives. They also can be used as the design models by working out of speed-controlled induction motors. Practical value. Operating characteristics of various speed-controlled induction electric drives are observed and depending on the chosen measure including measure of cost of losses of active energy, sampling of the best alternative of the drive is realized.